2015
DOI: 10.1039/c5ob00435g
|View full text |Cite
|
Sign up to set email alerts
|

Topochemical polymerization of unsymmetrical aryldiacetylene supramolecules with nitrophenyl substituents utilizing C–H⋯π interactions

Abstract: Diacetylenes are versatile building blocks, in which many functional groups can be incorporated for the construction of new materials with desirable properties. In this study, 6-(p or m-nitrophenyl)-3,5-hexadiyne-1-ol (4a or 4b) containing nitrophenyl groups (host) and 2-hydroxyethyl groups (guest) in different diacetylene terminals were designed to establish an ordered supramolecular assembly that is complied with the strict requirements for the topochemical polymerization of diacetylenes. Crystal film and bu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 51 publications
1
8
0
Order By: Relevance
“…As shown in Figure B, the original DA stretching band appears at 2267 cm −1 . After UV irradiation of the gel, two new peaks are seen, which were assigned to the typical conjugated alkyne–alkene structures of PDAs . This result confirmed that the 3 organogel was directly converted into its PDA by UV irradiation.…”
Section: Resultssupporting
confidence: 62%
See 1 more Smart Citation
“…As shown in Figure B, the original DA stretching band appears at 2267 cm −1 . After UV irradiation of the gel, two new peaks are seen, which were assigned to the typical conjugated alkyne–alkene structures of PDAs . This result confirmed that the 3 organogel was directly converted into its PDA by UV irradiation.…”
Section: Resultssupporting
confidence: 62%
“…Diacetylenes (DAs) can be polymerized via a photochemical or thermal process to a highly conjugated, rigid polydiacetylene (PDAs) system with unique chromatic properties . Importantly, the topochemical polymerization of DAs can only take place if these moieties are closely packed . Molecules linked to DA may become versatile building blocks for the construction of supramolecular polymeric structures .…”
Section: Introductionmentioning
confidence: 99%
“…1 In 1969, Wegner reported the rst example of diacetylene polymerisation in the solid state, 2,3 while 15 years later, Enkelmann proposed strict criteria for diacetylene reactivity, whereby adjacent diacetylene monomers will react when the reactive groups are separated by a C1-C4 0 contact distance (d) of #3.8Å, a translational period repeat spacing (r) of #4.9Å, along with an orientation angle (q) to the crystal axis at an optimum value of 45 (Scheme 1). [4][5][6] The diacetylene polymerisation parameters highlight the importance of molecular organisation in the topochemical reaction. 7,8 The monomer-to-polymer transition is clearly observed by a colour change from colourless to blue, due to the rearrangement of the diacetylene monomers to give an ene-yne chromophore.…”
Section: Introductionmentioning
confidence: 99%
“…48,49 Cocrystals of carboxylic acids can be prepared using the robust hydrogen-bonded COOH/N pyridine heterosynthon, while salts can be based on ammonium complexes of more basic amines. [50][51][52][53][54] In this work we explore the relationship between structure and photochemistry for PCDA (1) with three different pyridine-containing coformers 4,4 0 -azopyridine (2), 4,4 0 -bipyridyl (3), and trans-1,2-bis(4-pyridyl)ethylene (4) and compare the photoreactivity of the resulting cocrystals with aliphatic amine salts of 4,4 0 -bipiperidine (5), morpholine (6) diethylamine 7, and n-butylamine (8) (Scheme 2). To date no X-ray structure information has been reported for PCDA or related photoactive surfactant-like molecules despite its commercial importance and hence no structure-reactivity relationship has been elucidated.…”
Section: Introductionmentioning
confidence: 99%
“…The diyne systems are parallel as requested; nevertheless, the angle of the reactive carbons and mostly their distance separations are not favorable, being distorted and much too long, respectively (Figure 4). Topochemical polymerization of diacetylene is also prevented because there is no long range parallel stacking of diynes [58][59][60][61][62][63][64][65][66][67]. …”
Section: Crystallographic Studiesmentioning
confidence: 99%